Formulation and characterization of hybrid polymeric/ZnO nanocomposite coatings with remarkable anti-corrosion and hydrophobic characteristics - Ammar, Sh.; Ramesh, Kasi; Vengadaesvaran, B.; Ramesh, Subramaniam; Arof, Abdul Kariem (Springer Verlag, 2016)
In this study, ZnO nanoparticles ranging from 1 to 8% (w/w) were introduced into a hybrid acrylic-silicone polymeric matrix to achieve nanocomposite coating systems with remarkable anti-corrosion and hydrophobic characteristics. The chemical structure of the developed hybrid polymeric matrix was investigated using Fourier transform infrared spectroscopy, whereas the morphology and wettability of the developed surfaces were determined using field emission scanning electron microscopy and contact angle measurements (CA), respectively. Furthermore, the anti-corrosion performance and the barrier properties over 60 days of exposure to a 3.5% NaCl solution were studied by electrochemical impedance spectroscopy. All the obtained results revealed that the presence of ZnO nanoparticles significantly influences the performance of the acrylic-silicone polymeric matrix. A coating system with 3% wt ZnO nanoparticles demonstrated the most pronounced anti-corrosion properties and also achieved the highest CA, with a value of 95.6°.